The Jailed Sinoatrial Node: An Interesting Case of Cardiogenic Shock Secondary to Sinus Arrest Following Percutaneous Intervention - Ebubechukwu Ezeh MD; Esiemoghie Akhigbe MD; Mohammad Amro MD; Ebad Ur Rahman MD; Saad Malik MD; Kanaan Mansoor MD; Mehiar Elhamdani MD (SAGE Publishing, 2022)
Complete occlusion of the sinoatrial node artery can be a complication of percutaneous intervention (PCI) to the right coronary artery (RCA). When this happens, dysfunction of the sinus node may follow resulting in sinus arrest. When this occurs, it is usually transient and as such, is typically not accompanied by hemodynamic instability. Permanent sinus arrest and shock state may, however, occur on rare occasions. The presence of junctional rhythms on the electrocardiogram (ECG) may predict the occurrence of these permanent arrhythmias and cardiogenic shock. In this case report, we present a 78-year-old woman who developed cardiogenic shock secondary to sinus arrest following PCI to RCA. Her ECG showed junctional rhythm, and she went on to require permanent ventricular pacing. This illustrates a known but rare complication of PCI to RCA.